Congenital Erythropoietic Porphyria: Mild and Severe Form in Two Brothers - Purnachandra Badabagni; Ramadevi Birudala (Wolters Kluwer Medknow Publications, 2024)
Congenital erythropoietic porphyria (CEP) is an autosomal recessive inherited metabolic disorder caused due to deficiency of the enzyme uroporphyrinogen III cosynthase, resulting in large amounts of type I isomers, which massively accumulate in erythroid cells and then leak into plasma. CEP clinically presents as lifelong mutilating photosensitivity, erythrodontia, and hemolytic anemia. We report two brothers born out of consanguineous marriage with a diversity of features, i.e., mild and severe variants of CEP with hemolytic anemia and supported by genetic analysis.